Как Бабы-Яги сказку спасали - Мокиенко Михаил Юрьевич (Новые сказочные повести, 2018)
Экземпляры: ДО (20190204) / Инвентарный номер: 63510 / Цена: 91.00 / Сис.шифр: 84(2=411.2)6 / Авт.знак: М 74 / ГРНТИ: 17.82.93 / ББК: 84(2=411.2)6